Food Supplements and Functional Foods Assessment for Health and Nutrition Volume I - Domínguez Díaz, Laura; Cámara, Montaña; Fernández-Ruiz, Virginia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Nowadays, diet-related non-communicable diseases and their complications are one of the most important public health problems worldwide. Food supplements and functional foods are considered food products which contribute to the achievement of optimal nutritional well-being, health status, and quality of life through reducing the risk of diseases and promoting the appropriate function of human organs and systems. Nowadays, the assessment of these functional foods and the study of their implications in nutrition and health are important challenges in societies of developed countries where consumers increasingly demand foods with added value beyond the provision of nutrients and the satisfaction of appetite. In this reprint, the characterization of the nutritional composition and phytochemicals of functional foods and food supplements as well as the evaluation of their potential health benefits in different disorders and diseases through clinical trials or preliminary studies are addressed.